Worldview Formation, Reflexivity, and Personhood Their Essential Connectivity in Thick Perspective - Geiger, Matthew W. (2017)
This article is based on a collaborative ethnographic project involving three Episcopal high schools and explores how educating for worldview formation is necessarily educating for reflexivity and personhood. While religious educators frequently affirm the goal of worldview formation in religious education, a description of the practical and concrete ways in which this is a cultivation of human personhood is generally lacking. The article attempts to contribute a "thick" description of their essential connectivity and to point toward their vocational relevance.